PEMBINGKAIAN BERITA HUKUMAN MATI UNTUK KORUPTOR (Analisis Framing Wacana Hukuman Mati Untuk Koruptor di Tempo.co Periode 10 – 15 Desember 2019) - Risdianto, Danang; Wangi, Maya Sekar; Riyanto, Buddy (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
December 9, commemorated World Anti-Corruption Day, President Jokowi won the drama stage titled "Achievement Without Corruption" at SMK N 57 Jakarta. Jokowi said that the death penalty for corruptors could be applied if the people wanted. Related to this, of course, received attention from various media. Online media is one of the media that preaches the discourse of death penalty for corruptors, they update the latest news at each meeting. The online media which always preaches the discourse on death penalty for corruptors coherently in every meeting, Tempo.co This study aims to describe how Tempo.co frames the reporting of the death penalty discourse for corruptors. Release of Information about Coverage. Framing analysis was performed using the Zhongdang Pan and Gerald M. Kosicki analysis models using qualitative methods. The object of this research is Tempo.co with the unit of analysis of news related to the discourse of death penalty for corruptors from December 10-15, 2019. The results of the research show that Tempo's framing of the discourse on death penalty for corruptors puts forward not - disliked, because the death penalty would otherwise keep Indonesia from a more humane civilization. Keyword : framing analysis, death sentence for corruptors, Tempo.co